Viral Cre-LoxP tools aid genome engineering in mammalian cells. Issue 1 (December 2017) - Sengupta, Ranjita; Mendenhall, Amy; Sarkar, Nandita; Mukherjee, Chandreyee; Afshari, Amirali; Huang, Joseph; Lu, Biao
Abstract Background Targeted nucleases have transformed genome editing technology, providing more efficient methods to make targeted changes in mammalian genome. In parallel, there is an increasing demand of Cre-LoxP technology for complex genome manipulation such as large deletion, addition, gene fusion and conditional removal of gene sequences at the target site. However, an efficient and easy-to-use Cre-recombinase delivery system remains lacking. Results We designed and constructed two sets of expression vectors for Cre-recombinase using two highly efficient viral systems, the integrative lentivirus and non-integrative adeno associated virus. We demonstrate the effectiveness of those methods in Cre-delivery into stably-engineered HEK293 cells harboring LoxP-floxed red fluorescent protein (RFP) and puromycin (Puro) resistant reporters. The delivered Cre recombinase effectively excised the floxed RFP-Puro either directly or conditionally, therefore validating the function of these molecular tools. Given the convenient options of two selections markers, these viral-based systems offer a robust and easy-to-use tool for advanced genome editing, expanding complicated genome engineering to a variety of cell types and conditions. Conclusions We have developed and functionally validated two viral-based Cre-recombinase delivery systems for efficient genome manipulation in various mammalian cells. The ease of gene delivery with the built-in reporters and inducible element enables live cell monitoring, drug selection and temporal knockout, broadening applications of genome editing.